Re‐evaluation of Pre‐pump Arterial Pressure to Avoid Inadequate Dialysis and Hemolysis: Importance of Prepump Arterial Pressure Monitoring in Hemodialysis Patients. Issue 7 (1st May 2015) - Shibata, Eriko; Nagai, Kojiro; Takeuchi, Risa; Noda, Yasuhiro; Makino, Tomomi; Chikata, Yusuke; Hann, Michael; Yoshimoto, Sakiya; Ono, Hiroyuki; Ueda, Sayo; Tamaki, Masanori; Murakami, Taichi; et al.
Abstract Prepump arterial pressure (PreAP) is monitored to avoid generating excessive negative pressure. The National Kidney Foundation K/DOQI clinical practice guidelines for vascular access recommend that PreAP should not fall below −250 mm Hg because excessive negative PreAP can lead to a decrease in the delivery of blood flow, inadequate dialysis, and hemolysis. Nonetheless, these recommendations are consistently disregarded in clinical practice and pressure sensors are often removed from the dialysis circuit. Thus far, delivered blood flow has been reported to decrease at values more negative than −150 mm Hg of PreAP. These values have been analyzed by an ultrasonic flowmeter and not directly measured. Furthermore, no known group has evaluated whether PreAP‐induced hemolysis occurs at a particular threshold. Therefore, the aim of this study was to clarify the importance of PreAP in the prediction of inadequate dialysis and hemolysis. By using different diameter needles, human blood samples from healthy volunteers were circulated in a closed dialysis circuit. The relationship between PreAP and delivered blood flow or PreAP and hemolysis was investigated. We also investigated the optimal value for PreAP using several empirical monitoring methods, such as a pressure pillow. Our investigation indicated that PreAP is a critical factor in the determination of delivered blood flow and hemolysis, both of which occured at pressure values more negative than −150 mm Hg. With the exception of direct pressure monitoring, commonly used monitoring methods for PreAP were determined to be ineffective. We propose that the use of a vacuum monitor would permit regular measurement of PreAP.